Rafał Kania, Myśl polityczno-prawna Franciszka Ksawerego Szaniawskiego (1768-1830), 2012 - Justyński, Janusz (Czasopismo Prawno-Historyczne, 2018)
Rafał Kania, Myśl polityczno-prawna Franciszka Ksawerego Szaniawskiego (1768-1830), 2012